House dust mold in Istanbul. I. Detection of mold flora in bed dust [Istanbul'da ev tozu küfleri üzerine çalişmalar. I. Yatak tozu küf florasinin saptanmasi.] - (:unkn) unknown (My University, 1988)
In our study, mycological analyses were carried out on 110 randomly chosen houses for bed dusts. 748 mould strains belonging to 117 genus and species were isolated and identified. Air-borne pathogenic fungi, fungi that are causative agents of pulmonary allergy such as Cladosporium spp., Aspergillus glaucus group, Alternaria, Ulocladium, Aureobasidium pullulans, Aspergillus niger group were isolated.